Urinary Incontinence and Overactive Bladder Symptoms in Women with Breast Cancer Being Treated with Oral Hormone Therapy - Rebeca Stahlschmidt; Amanda Canato Ferracini; Luana Moreira de Medeiros; Cinthia Madeira de Souza; Cassia Raquel Teatin Juliato; Priscila Gava Mazzola
Abstract Objective: The objective of the present study is to observe the frequency and severity of urinary symptoms in women with breast cancer (BC) being treated with oral hormone therapy, associating them to drug adherence. Methods: The participants were interviewed once from June to October 2016. The evaluation of urinary symptoms was performed by two questionnaires: International Consultation on Incontinence Questionnaire - Short Form (ICIQ-SF) and International Consultation on Incontinence Questionnaire Overactive Bladder Module (ICIQ-OAB). Adherence was evaluated by the Morisky-Green method. Statistical analysis was performed by the Mann-Whitney test, linear regression, and Spearman correlation. Results: Fifty-eight women were interviewed: 42 treated with tamoxifen and 16 with aromatase inhibitor. Twenty-seven women (46.5%) presented urinary incontinence symptoms and 15 (25.8%) presented stress urinary incontinence (SUI). Fourteen (24.1%) women had symptoms of overactive bladder (OAB). There was no statistical difference in symptoms between both treatments and duration of treatments. Higher scores in the ICIQ-SF questionnaire were associated with low/medium adherence and advanced age. Higher scores in the ICIQ-OAB questionnaire were associated with low/medium adherence. Conclusion: The present study showed a high prevalence of urinary symptoms, such as urinary incontinence and OAB, associated with low/medium adherence and older age in women with BC being treated with oral hormone therapy. Health professionals should be alert to these symptoms since it could influence life quality and adherence to treatment.